Laparotomy for Ingested Foreign Body in Children: Nine Years Experience in A Tertiary Care Hospital (Dhaka Shishu (Children) Hospital Journal, 2024)
Background: Ingestion of foreign bodies in children is a common occurrence and can affect from harmless to life-threatening situations. While laparotomy for ingested foreign body, in children is generally safe and effective, it is more important to take steps to prevent foreign body ingestion in the first place. Objective: The aim of this study was to evaluate the cases that underwent laparotomy for foreign body ingestion and the management of any complications. Methods: This retrospective study was conducted in the Division of Paediatric Surgery, Bangladesh Shishu Hospital & Ins titute, Dhaka, Bangladesh from January 2013 to December 2022. Total 83 patients were admitted for ingestion of foreign body of which 32 foreign bodies were removed endoscopically and 40 patients expelled foreign bodies with defecation without any intervention. For the remaining 11 patients, laparotomy was performed and associated complications were managed accordingly. Results: In this study, the average age of the children were 38.7 months, of which majority were male (81.8%). Common presenting symptoms were dysphagia, (18.2%), abdominal pain (45.5%), vomiting (27.3%), and fever (27.3%). Whereas,36.4% were asymptomatic. The time interval between ingestion and treatment were about 56.5 hours. The primary indication for laparotomy was perforation (45.5%) and failed endoscopic removal (36.4%). Most ingested objects were magnets (36.4%), predominantly found in the jejunum and ileum (45.5%). The commonest per operative complication (81.8%) was intestinal obstruction. The average operation time was 68.4 minutes. Post-operative hospital stay was 7.5 days on average, with a 4.2-month follow-up. There were incidents of postoperative complications, with 18.2% experiencing postoperative ileus. Conclusion: Careful follow up of children with Ingested foreign bodies specially sharp and pointed objects, is warranted for its occasional requirement of surgical intervention, predominantly due to failure of endoscopic removal or spontaneous passage. Multiple ingestion of magnets or a single button battery ingestion can lead to life threatening complications, requiring surgical intervention.DS (Child) H J 2023; 39(1): 36-43